Resmin dokunması - (:unkn) unknown (My University, 2012)
14-19. yüzyıllar arasında özellikle Kuzey Avrupa’dan başlayarak tüm Avrupa’ya yayılan “tapestry” geleneği tekstil sanatı içinde son derece önemli ve ayrıcalıklı bir yere sahiptir. Tekstillerin baş tacı olarak kabul edilen tapestryler gücün, zenginliğin sembolleri ve bir statü göstergesi niteliğine sahiptir. Avrupa kiliselerinin ve saraylarının en önemli iç mekân dekorasyon unsuru olan tapestrylere sahip olma ayrıcalığı sadece varlıklı kişiler ve özellikle kraliyet ailesine aittir. Siparişlere ve mimariye bağlı olarak son derece büyük ebatlarda, tek parça ya da birden çok parçadan oluşan setler halinde üretilmişlerdir. Genellikle figüratif özelliklere sahip olan kompozisyonlar, av sahneleri, manzara, alegorik tasvirler, dinsel ve mitolojik konulardan oluşmaktadır. Avrupa’nın birçok bölgesinde üretim merkezleri olan tapestryler 15-18. yüzyılda altın çağını yaşamıştır. Önemli üretim merkezleri arasında Flandra, Arras, Brüksel, Tournai, Gobelins, Beauvais ve Aubosson atölyeleri bulunmaktadır. 19. yüzyıldan itibaren sanayi devrimi ile birlikte önemini ve gücünü kaybeden tapestry üretimi giderek kaybolmuştur. Yüzyılın sonlarında William Morris’in öncülük ettiği Art&Crafts (Sanat ve Zanaat) hareketi tapestry üretiminin yeniden canlanmasına önemli katkı sağlamıştır. Avangard ve modernizmin getirdiği modern sanatın hareketlerine bağlı olarak ortaya çıkan değişim sürecinde, tapestry geleneği dönemin öncü sanatçılarının dikkatini çeker ve sanatçılar tablolarını tapestry tekniğinde dokutmaya başlar. İşlev ve amaç bakımından tapestry geleneğinden kopmuş olsalar da bu dokumalar 20. yüzyılın tapestrylerini oluşturmaktadır. Bu makalede, geleneksel tapestrylerin değişim süreci, nedenleri, amaçları ve sonuçlarının tartışılması ve değerlendirilmesi amaçlanmaktadır.

The tradition of “tapestry”, which originated in Northern Europe between 14th – 19th centuries and spread to the whole Europe, has a quite important and privileged place in the art of textile. Tapestries, regarded as masterpieces of tapestries, are symbols of power and wealth, and indicative of status. The privilege of owning tapestries, which are the elements of interior decoration in European churches and palaces, only belongs to wealthy people and especially to royal families. Tapestries have been produced based on orders and architecture, and in huge dimensions, in single pieces or multiple-piece sets. Because of their portability in rolls, they were also named as “mobile murals”, and decorated the walls of European churches and palaces. Vignettes, which portray strong observations on the daily life and human nature of the Middle Age, frequently reflected subjects such as hunting scenes, which activity was a popular aristocratic engagement of the period, scenery and country representations often intensified with human figure in composition fictions, allegorical portrayals on life and death, religious and mythological subjects and allegorical descriptions of months and years. Vignettes were used as decoration elements in special occasions such as christening ceremonies, official dines, wedding ceremonies, diplomatic receptions and funerals. The area fronts of municipal houses were decorated with tapestries during corteges. Tapestries have also been used as wedding gifts and diplomatic gifts. Tapestries, of which the production started throughout Europe by 1400s, had their golden era between 15th and 18th centuries, in terms of their qualities and prevalence. Weaving intensified especially in south part of Holland, Flandre, (Northeast of Belgium) and France. Arras and Brussels were the prominent production centers. Tournai joined these in the 15th century. Carrying its quality of being an important weaving center in Flandre in 14th century into the 15th century, Arras developed especially on the support of Burgonya workshop. It is stated that approximately 60 weaving masters worked at the sources. The dukes of Burgonya started to support Tournai instead of Arras after 1450s, and later on, the workshops in Brussels developed in the second half of the 15th century. Tapestry production is seen in Italia in such regions as Ferrara, Mantova and Florence in 1500s. Named “arazzo” in Italy, this weaving type is described as the inter section of artisanal production and artistic production. Production in workshops supported by Medici Family continued until the 18th century. Cardboards prepared by artists such as Bronzino and Bachiacca had previously been weaved by explorer Dutchman weavers. Among many other artists, Raphael and Rubens are of the artists who prepared tapestry patterns in this period. In the 18th century Flemish workshops went into a gradual decline. With closing of the last weaving workshop in Brussels in 1794, France took the crown from Flandre. The most important production centers of France in the 17th century are Gobelins, Beauvais and Aubosson workshops. Of these, Gobelins Production, which outshone the others, was established in Paris in 1662 and in a short time united many workshops under its roof, and made the name “Gobelins” a synonym for tapestry. Gobelins Factory, established on entrepreneurship of Colbert, the Revenue Minister of Louis XIV, has carried on its production until today. While Gobelins Factory produced for the industry, Beauvais Factory which was established in 1664 by two Dutchmen named Louis Hinart and Philippe Behagle, served the noble and wealthy bourgeoisie, under protection of the Palace. On the other hand, Aubusson, which had been active as a private workshop for over a hundred years, was converted into the royal factory in 1962. Losing its importance and strength with the industrial revolution after the 19th century tapestry production diminished gradually. It was later revived by the Arts & Crafts movement pioneered by William Morris through the end of the century. William Morris established the William & Co. Company as a handmade production and decoration firm. Morris, besides his variety of productions such as handmade furniture and wallpapers, also established the Merton Abbey Workshop in 1881, thus influencing revival of tapestry workshops by starting tapestry production. Also an important breakthrough happened with the Bauhaus in the 20th century. Aiming to unite applied arts with fine arts towards the goal of reviving collocation of art and craft, the Bauhaus School and organization movements contributed in reviving tapestry production and supported re-opening of workshops. Granted administration of tapestry industry over request of the French government, Jean Lurçat (1892-1966) enabled revival of Aubusson workshops. Jean Lurçat, regarded as the most important tapestry artist of the century, influenced the contemporary artists both with his productions and his highlighting the importance of the splendor and spatial place of tapestry, and mediated that the works of artists such as Picasso, Braque, Matisse, Leger and Miro, pioneers of modern art, be weaved in Aubusson workshops. This movement likewise induced revival in other European workshops, which we observe today as the tapestry in 20th century. In this period which featured tapestries changed and differentiated, we observe that the most influential name in attraction of certain Turkish painting masters to this subject is again Jean Lurçat. The fact that Jean Lurçat was lectured in Istanbul State Academy of Fine Arts by Zeki Faik Izer is an important factor in formation and development of weaving painting art in Turkey. In this subject which attracted the young students of the academy, the first attempt was made by Ozdemir Altan. Ozdemir Altan actualized weaving with Omer Karacam, Zeki Alpan and Zekai Ormancı in his workshop which he set up in Cihangir. Just like carpets in Anatolia are named after the place they are woven, the artists named his products as “Cihangir Carpets”. It was Faik Izer who fostered Ozdemir Altan to the adventure of weaving painting, yet we see the works of the artist in this field in 80s. Another master who re-interpreted his paintings as weavings was Devrim Erbil. The first of these works, which he himself named as Haliresim (Carpet Painting) is the rug weaving named as “Kalkan Agaci” (“Shield Tree”) woven in Cihangir workshop of Ozdemir Altan, in 180x130cm dimensions. Another artist still carrying on production in this area is Burhan Dogancay. Dogancay’s works named “Kurdeleler ve Golgeleri” (“Braids and Their Shadows”) are being produced in Raymond Picaud workshop in Aubusson, one of the most important tapestry production centers of France, since 1983. Another artist of the masters of Turkish Painting Art who re-interpreted his paintings as weavings in 2010 is Mustafa Aslier. Tapestries, of which types and reasons of production varied as from the 20th century, are exhibited as tapestry tradition expressed in weavings of modern art masters’ paintings, within the change process emerging in connection with the modern art movements brought by Avant-Garde and modernism. Though they are separated from the tapestry tradition in terms of function and objective, these weavings form the 20th century tapestry. This article describes the process of change in the traditional tapestry, causes, purposes and results of the discussion and analysis.
Weaving of painting